2022
DOI: 10.3390/ijerph192114354
|View full text |Cite
|
Sign up to set email alerts
|

Slack Resources, Corporate Performance, and COVID-19 Pandemic: Evidence from China

Abstract: COVID-19 has caused tremendous damage to global economies, and similar health crises are expected to happen again. This study tests whether slack resources would enable companies to prepare for such uncertainties. Specifically, we explored the influence of the COVID-19 patient occurrence on corporate financial performance and the buffering effect of financial slacks using Chinese listed companies’ data during 2021. We also examined whether this effect differs across firms’ financial health and industry. Test r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…They argue that high levels of slack lead to inefficient investment decisions and generate opportunity costs which add rigidity to a firm [33,44]. This is supported by some studies, which show an inversed U-shape relationship between slack and corporate outcomes such as innovation or financial performance [42]. As our study focuses on manufacturing SMEs which are generally regarded as not resource-rich, this curvilinear relationship should not be a concern.…”
Section: Financial Slack and Strategic Changesupporting
confidence: 65%
See 1 more Smart Citation
“…They argue that high levels of slack lead to inefficient investment decisions and generate opportunity costs which add rigidity to a firm [33,44]. This is supported by some studies, which show an inversed U-shape relationship between slack and corporate outcomes such as innovation or financial performance [42]. As our study focuses on manufacturing SMEs which are generally regarded as not resource-rich, this curvilinear relationship should not be a concern.…”
Section: Financial Slack and Strategic Changesupporting
confidence: 65%
“…There is a substantial amount of research related to the importance of slack, including the seminal papers by Bourgeois [38], Nohria and Gulati [39], and Singh [40]. Buffering and facilitating are frequently cited in the literature as the important roles of slack in times of crisis [41][42][43]. As Lefebvre succinctly states, "slack resources serve the functions of stabilizing and adapting that help firms deal with external shocks and explore additional, riskier business opportunities .…”
Section: Financial Slack and Strategic Changementioning
confidence: 99%
“…Zhang & Zhang (2021) showed that a higher number of COVID-19 cases significantly decreased profitability in 107 countries. Moreover, Jin et al (2022) confirmed that over the period of COVID-19 spread (2020), the profitability of Chinese-listed firms was significantly and inversely affected.…”
Section: Introductionmentioning
confidence: 52%
“…Through methods and techniques of financial analysis, financial performance describes the achieved corporate financial health (Durica et al 2023;Kaczmarek et al 2021). According to Hedija and Nemec (2021), Jin et al (2022), andKayani et al (2023), data collected through financial performance evaluations have significant explanatory power. Many authors employ intricately constructed systems of indicators or constructed models that are separated into several parts to evaluate the performance of firms (e.g., in terms of labor productivity growth-Lăzăroiu and Rogalska 2023, of deliberate managerial strategy- Vătămănescu et al 2020, andof organizational achievements-Vătămănescu et al 2023) with the intention of introducing a more detailed comprehension of the achieved corporate performance.…”
Section: Literature Reviewmentioning
confidence: 99%